Correlation of basic motor skills with arthroscopic experience - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2009)
Objectives: One of the methods in motor skill teaching is to furnish the students with the individual skills drawn from the target procedure. This method requires identification and defining of all components of the target procedure. This study aimed to define basic motor skills composing arthroscopic skillfulness. Methods: A total of 42 orthopedists (mean age 38 +/- 8 years) were enrolled. The Study group was comprised of 17 experienced orthopedists working at least for 10 years as a specialist and performing more than 50 arthroscopic procedures per year. The control group included 25 young orthopedists or residents having an arthroscopic experience of less than three years. All the participants were assessed simultaneously and in the same experimental setting. Each participant was tested after having been shown to use in vitro skill development instruments simulating arthroscopic basic motor skills. Results: Compared to the control group, the experienced group had significantly higher mean age (42 vs. 34.4 years), longer duration of arthroscopic experience (12.4 vs. 1.6 years), and greater number of the arthroscopies performed per year (93.9 vs. 26.9) (p=0.000). The mean anticipation time (p=0.028) and two-arm coordination time (p=0.043) were significantly shorter in the experienced group. In correlation analysis, duration of arthroscopic experience was correlated with the mean anticipation time (r=-0.41, p=0.008) and two-arm coordination time (r=-0.33. p=0.033). In addition, the mean anticipation time decreased significantly as the number of arthroscopies increased (r=-0.446, p=0.003). Conclusion: Some basic motor skills correlate with arthroscopic competence. The use of these motor skill instruments in arthroscopy training may aid to improve arthroscopic skills.
Keywords: Arthroscopy/education; clinical competence; kinesthesis; motor skills; psychomotor performance; task performance and analysis; time perception; EDUCATION